Réponses

  • Utilisateur Brainly
2014-04-30T13:10:23+02:00

A = x(y+2)
 B = 3x(x-2)
C = (x-2)(x+3+3x-1)
   = (x-2)(4x+2)
   = 2(x-2)(2x+1)
D = (2x-1)(x+3+1)
   = (2x-1)(x+4)

E  = (x-3)²
F =(2y+5)²
G =(6-)(6+k)
H = (5-x-3)(5-x+3)
   = (-x+2)(-x+8)
2014-04-30T13:36:58+02:00
Exo 1 :
A= 3(x+2) -x(3x+1)
=3x+6-3xau carré-x
=-3xau carré +2x-6

B= (x-4)(5x+1)
= 5xau carré +x -20x -4
=5xau carré-19x-4

C= (1-7x)(1+7x)
=1-49xau carré

D= (1/5 -5a)au carré
= 1/25-2+25a au carré
= 25a au carré -49/25

J=xau cube -25x
= x(xau carré -25)

K=xau carré -4+(x-5)(x+2)
= xau carré -4+ x au carré +2x-5x-10
= 2x au carré-3x-14
= 2x(x-3-7)

Exo 3 :

2x=-6/5
x=-6/5 :2
x=-6/5 x 1/2
x=-6/10


8x-1=5x+1
8x-5x=-1+1
3x= 0
x= 0

3(x-2)=2(x+3)
3x-6=2x+6
3x-2x=6+6
x=12